Financiamiento del activo fijo como herramienta estratégica para la modernización y productividad del Molino El Comanche SRL, distrito de San José, Año 2018 - Muñoz Usquiza, Estefani Jackeline (2019)
The present investigation is referring to the financing of fixed assets as a strategic tool for the modernization and productivity of the Comanche SRL mill, located in the District of San José, 2018; its type of research is applied because it makes use of technical instruments of different disciplines linked to the accounting and financial environment and is also descriptive because its foundation is the study of the characteristics of the variables; This research project has as a line of research financial accounting, which is responsible for collecting, classifying, recording, summarizing and reporting on transactions valued in money by an economic entity, which will be developed based on a schedule of work established where the start date and end of the project consists, we will also have personal resources, goods and services which will be self-financed. It also has a problematic reality in which it describes that in the international sphere the most innovative financial institutions have developed diverse experiences and adequate technologies to satisfy the demand of agricultural trade financing, some of the initiatives are to design financial products, among them credits, that respond to the needs of the merchants. Regarding the national use sources and policies for the financing of fixed assets in the short term, because they are very varied, since all business transactions of a company are made by this means, since the objective of their capital investment it is directly related to productivity. We also determine the problem and the formulation of the hypothesis will see how the financing of fixed assets as a strategic tool will allow the modernization and productivity of the entity, we also have objectives such as analyzing the economic and financial situation of the company; as well as assess the degree of modernization in which the company is located.